Hubungan Self-Efficacy Akademik dan Motivasi Akademik Terhadap Hasil Belajar Ekonomi Siswa Kelas X SMA Negeri 12 Surabaya - Rachmawati, Nilam Septi Ariria; Nurlaili, Eka Indah (Jurnal Pendidikan Ekonomi (JUPE), 2024)
The aim of this study is to analyze the partial and simultaneous relationships between academic self-efficacy and academic motivation towards the learning outcomes of 10th-grade students at SMA Negeri 12 Surabaya in the subject of economics. A quantitative approach is utilized in this research, with a focus on descriptive analysis and multiple linear regression. Data collection method involves the use of questionnaires. The research population consists of 365 students, with a sample size of 191 students selected using the Simple Random Sampling method. The analysis results indicate that there is a significant partial and simultaneous influence on student learning outcomes. A significant positive relationship between academic self-efficacy and economics learning outcomes of students is shown by the value of sig. 0.000 < 0.05. The higher the level of academic self-efficacy of students, the greater their achievement in economics learning outcomes. However, there is a significant negative relationship between academic motivation and economics learning outcomes of students, indicated by the value of sig. 0.000 < 0.05. This means that the higher the level of academic motivation of students, the lower their achievement in economics learning outcomes.